(untitled) (Perioperaciina Medicina, 2020)
The experience of using dexmedetomedine for sedation with respiratory disorders of varying severity has been known for a long time. This article examined two clinical cases in which dexmedetomedine was used for connection and adaptation of patients to mechanical ventilation of lungs. The purpose of the work is evaluation of the effectiveness and depth of sedation with varying degrees of respiratory failure, as well as the effect of dexmedetomedine on respiration.